Communication Pattern in Balinese Family (A Study of Nuclear Family’s Communication Pattern in Communicating Bali Aga’s Custom in Tenganan Pegringsingan, Karangasem, Bali) - Ni Made Yeni Sudaryati (The Indonesian Journal of Communication Studies, 2008)
Custom and family have a very close relationship, particularly in continuing the ancestors’ tradition that exists in Tenganan Pegringsingan. In doing this role, there is an interpersonal communication between parents and children. This article explores interpersonal communication pattern in nuclear family in order to maintain ancestors’ tradition in Tenganan Pegringsingan that still survive until today. The theories applied are interpersonal communication, family, and society’s culture in Tenganan Pegringsingan that deals with the everlasting custom in Bali Aga in Tegangan Pegringsingan itself. Through communication pattern in the nuclear family, communication is an important factor determining the continuance of tradition that exists in Bali Aga village, Tenganan Pegringsingan, Karangasem, Bali.